The Parlour and the Suburb: Domestic Identities, Class, Femininity and Modernity - Belisle, Donica (Labour / Le Travail, 2008)
The article reviews the book, "The Parlour & the Suburb: Domestic Identities, Class, Femininity and Modernity," by Judy Giles.
Keywords: BOOKS – Reviews; GILES; Judy; Nonfiction; PARLOUR & the Suburb: Domestic Identities; Class; Femininity & Modernity; The (Book); WOMEN in development